Phytochemical Screening, Antioxidant, and Antibacterial Activity of Dioon spinulosum Dyer ex Eichl.: Phytochemical Screening, Antioxidant, and Antibacterial Activity of Dioon spinulosum Dyer ex Eichl. - Nair, Laija S. (International Journal of Pharmaceutical & Biological Archive, 2020)
The present study was aimed to investigate the phytochemical, antioxidant, and antibacterial studies of leaf and rachis of Dioon spinulosum Dyer ex Eichl. The phytochemical screening of the plant extracts revealed the presence of alkaloids, flavonoids, tannins, terpenoids, carbohydrate, and phenols, whereas saponin was absent. The phenolic content expressed as mg/g gallic acid equivalent was determined and was more in methanolic extract of leaf (29.40 mg) than rachis (8.76 mg). Flavonoid contents were also greater in leaves than in rachis and methanol extract contained higher content (2.812 mg/g) than water (1.923 mg/g). Terpenoids were more in the aqueous extracts of both leaf and rachis when compared to methanol extracts. Antioxidant activity of both leaf and rachis extracts was conducted using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power assay. Leaf extract showed more DPPH radical scavenging activity with IC50 value of 130 Î¼g/ml when compared to the rachis of D. spinulosum Dyer ex Eichl. The reducing capability of the leaf extract was found to be more when compared to rachis. The antibacterial potential was evaluated with Staphylococcus aureus and Streptococcus mutans by agar well diffusion method. Antibacterial activity was observed only at higher concentration (1000 Î¼g/ml) with inhibition zones of 12 mm and 13 mm.